2018
DOI: 10.1007/s00430-018-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine responses in Rickettsia felis infected febrile children, Ghana

Abstract: The intracellular pathogen Rickettsia felis causes flea-borne spotted fever and is increasingly recognized as an emerging cause of febrile illness in Africa, where co-infection with Plasmodium falciparum is common. Rickettsiae invade endothelial cells. Little is known, however, about the early immune responses to infection. In this study, we characterize for the first time the cytokine profile in the acute phase of illness caused by R. felis infection, as well as in plasmodial co-infection, using serum from 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Levels of IL-8, IP-10, MCP-1 and MIG showed a significantly high increase in patients upon admission compared to the controls. These chemokine levels are consistent with those reported in pediatric patients infected with R. felis during the acute phase, where IL-8, IP-10, and MCP-1 attract immune cells to infection sites and likely reflect initial host responses to R. rickettsii (8). Plasma levels of IL-10, a potent inhibitor of TNFα and IL-6, were found to be significantly increased in patients upon admission to hospital.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Levels of IL-8, IP-10, MCP-1 and MIG showed a significantly high increase in patients upon admission compared to the controls. These chemokine levels are consistent with those reported in pediatric patients infected with R. felis during the acute phase, where IL-8, IP-10, and MCP-1 attract immune cells to infection sites and likely reflect initial host responses to R. rickettsii (8). Plasma levels of IL-10, a potent inhibitor of TNFα and IL-6, were found to be significantly increased in patients upon admission to hospital.…”
Section: Discussionsupporting
confidence: 87%
“…In the present pilot study, it was observed that in pediatric patients with RMSF it was characterized by a systemic increase in several pro-inflammatory cytokines such as IL-6 and IL-8. This increase has also been reported in other studies of patients with RMSF (8,18,19) reflecting the activation of monocytes / macrophages and endothelial cells infected by rickettsia, and attraction of T and NK lymphocytes (20,21).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Coinfections make the diagnosis a challenge; they assert the clinical status of the patient, complicate the treatment, and presumably, in some cases, they work in a symbiotic way or are synergistic (16,17,24). A few cases of coinfections with rickettsial diseases have been reported in Mexico, as reported by In contrast to results obtained by Rauch et al, 2018 in our study a significant difference was found between the co-infected and mono-infected groups, in which R. rickettsii was involved; this could be as a result of the aforementioned, which in some cases of co-infection, the mechanism of action of the pathogens involved boost or act synergistically, increasing the extent of the injury, severity, and complexity of the clinical picture.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 96%